2007
DOI: 10.3892/ijmm.19.4.659
|View full text |Cite
|
Sign up to set email alerts
|

Association of total plasma homocysteine with methylenetetrahydrofolate reductase genotypes 677C>T, 1298A>C, and 1793G>A and the corresponding haplotypes in Swedish children and adolescents

Abstract: We studied 692 Swedish children and adolescents (aged 9-10 or 15-16 years, respectively), in order to evaluate the effect of the methylenetetrahydrofolate reductase (MTHFR) 677C>T, 1298A>C, and 1793G>A polymorphisms on total plasma homocysteine concentrations (tHcy). Genotyping was performed with Pyrosequencing™ technology. The MTHFR 677C>T polymorphism was associated with increased tHcy concentrations in both the children and the adolescents (P<0.001 for both age groups) in both genders. The effect of MTHFR 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 26 publications
6
45
1
Order By: Relevance
“…A previous study indicated the effects of plasma homocysteine level on the association between C677T and A1298C or G1793A (3). Further studies are required to determine the effects of fitness on the association between arterial stiffness and MTHFR haplotype.…”
Section: Discussionmentioning
confidence: 98%
“…A previous study indicated the effects of plasma homocysteine level on the association between C677T and A1298C or G1793A (3). Further studies are required to determine the effects of fitness on the association between arterial stiffness and MTHFR haplotype.…”
Section: Discussionmentioning
confidence: 98%
“…The control group consisted of 1,079 individuals from a cross-sectional population studied in central Sweden, the same area in which our group of infertile women was recruited. The data concerning the control individuals have already been published (19)(20)(21)(22).…”
Section: Materials and Methods Subjectsmentioning
confidence: 99%
“…Previously described Pyrosequencing assays (19)(20)(21)(22) (Biotage AB, Uppsala, Sweden) were used to genotype the polymor-…”
Section: Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the carriers of the 677TT genotype accumulate formylated folates, which points to a disruption of the folate cycle [25,26]. The 677C>T substitution is the most common missense variation of MTHFR , with a global prevalence of 40% [25].…”
Section: Mthfr Genementioning
confidence: 99%